2016
DOI: 10.1210/jc.2016-2701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conjugated Linoleic Acid and Metformin on Insulin Sensitivity in Obese Children: Randomized Clinical Trial

Abstract: Improvement of insulin sensitivity, measured via euglycemic-hyperinsulinemic clamp and IRS2 upregulation, favored patients treated with CLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Oleic acid [50,51] and linoleic acid [52,53] have been reported to have beneficial effects on metabolic disease. In the current study, we found that these fatty acids occupy more than half of BO (online suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Oleic acid [50,51] and linoleic acid [52,53] have been reported to have beneficial effects on metabolic disease. In the current study, we found that these fatty acids occupy more than half of BO (online suppl.…”
Section: Discussionmentioning
confidence: 99%
“…All included studies were written in English and published between 2001 and 2017. Among these 38 included studies, 10 studies were done in Europe, 12,20,23,25,31,34,42,44,48,49 20 in the United States and Canada, 10,17,18,21,22,24,29,30,33,35,36,[39][40][41]43,45,47,50,51 3 in Middle America, 11,27,28 1 in Africa (Egypt), 26 and the remaining 2 studies in Asia (Iran). 19,46 In addition, two studies were done among populations from different countries.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…19,46 In addition, two studies were done among populations from different countries. 32,37 Out of included studies, 12 studies were performed in children 17,25,27,28,31,32,39,40,42,[44][45][46]51 and 25 studies in adolescents. [10][11][12][18][19][20][21][22][23][24]26,29,30,[33][34][35][36][37][38]41,43,[47][48][49][50] In addition, six studies were conducted in female participants, 21,26,30,31,44,47 while the others recruited participants from both genders.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations